METODE PEMBELAJARAN KOSAKATA - Kastam Syamsi, Kastam Syamsi (Cakrawala Pendidikan, 1998)
Vocabulary teaching is one of the important aspects oflanguage teaching. Actually, vocabulary teaching is one of theoldest areas of interest in educational research. But, it is notgaining much attention.There are two conlmon types of vocabulary teachingmethods, namely, direct and indirect ones. Direct nlethods coverall methods directly presenting vocabulary as instructionalmaterial, such as, defi~~itionanl d contcxlual methods, whercasindirect methods cover various language activities supportingvocabulary teaching, including reading, listening, speaking, andwriting. With various research results as basis, it can beconcluded that there is no one single method which is the best.Every method has its special characteristics. The teacher shoulduse various methods in teaching vocabulary, while, on the otherhand, extensive reading is one of the resources for vocabularydevelopment.